103k views
5 votes
Solve the equation
4x^3
- x=0

Solve the equation 4x^3 - x=0-example-1
User Fahim
by
4.9k points

2 Answers

3 votes

Answer:


x=0, (1)/(2), -(1)/(2)

Explanation:


4x^3-x=0 \\\\x(4x^2-1)=0 \\\\x(2x-1)(2x+1)=0 \\\\x=0, (1)/(2), -(1)/(2)

Hope this helps!

User Lorelle
by
4.8k points
4 votes

Answer:

x=0 x = 1/2 x = -1/2

Explanation:

4x^3 - x=0

Factor out an x

x(4x^2 -1) =0

Factor inside the parentheses ( difference of squares a^2 -b^2 = (a-b)(a+b))

x (2x-1)(2x+1) =0

Using the zero product property

x=0 2x-1 =0 2x+1 =0

x =0 2x=1 2x = -1

x=0 x = 1/2 x = -1/2

User Mismas
by
4.9k points